Contemporary Dai folk song in Xishuang Banna by Yuguang: June Spring Warm Look Forward to Lovers - Shengchuan Ruij (Journal of Green Learning, 2022)
The objective of this paper was to study the “June spring warm look forward to lovers,” which was composed by Yuguang in Ga Sa Village, Xishuang Banna, Yunnan Province, China. Field study in 2021, using an anthropological approach to explicate characteristics of Yuguang's contemporary compositions, based on Dai culture and Zhangha cultural symbol. The results of the study were as follows: “Zhangha, a cultural symbol, constitutes the materialized carrier of people's concept of the harmonious special culture of people under the unique context and religious spirit of the Dai people. The structure was similar to the rondo form or ABACADAEFA. The composer has created and stands out  as follows: The traditional melody of “Zhang-ha”, which makes its apperance in the accompaniment timbre, breaks through the single technique, thus generating this modern Dai song. There are two interesting musical characteristics: 1) It vividly depicts the lively and jubilant scene of guests arriving to celebrate the new year in the Dai New Year, with a beautiful, vivid melody and passionate lyrics. That describes the happy and sweet mood of lovers when they get together. 2) The song’s musical structure is a typical multi-periodvariation structure. At the same time, the rhythm of the whole song is distinct, and the melody range changes freely.